New Approach to Formulation of Universal Laws on the Basis of Formalism of Spinor Field Theory - N. M. Sokolova (Наука и техника)
The paper substantiates a new approach, which is called «a spinor one» by the author, to construction of models of various objects, systems and processes by means of analogies with calibrated theory of physical vacuum.The spinor approach combines not only all three well-known methods (thermodynamic, static and synergetic) but it also has some significant advantages. This approach makes it possible to describe «physical vacuum» beyond theory of relativity, to classify new structures and their parameters that are initiated at the unstable points in the case of non-equilibrium transitions, to determine structural and dynamic stability and instability in the investigated phenomena.